Microstructural Characterization of a Laser Surface Remelted Cu-Based Shape Memory Alloy - Silva,Murillo Romero da (2018)
Cu-based shape memory alloys (SMAs) present some advantages as higher transformation temperatures, lower costs and are easier to process than traditional Ti-based SMAs but they also show some disadvantages as low ductility and higher tendency for intergranular cracking. Several studies have sought for a way to improve the mechanical properties of these alloys and microstructural refinement has been frequently used. It can be obtained by laser remelting treatments. The aim of the present work was to investigate the influence of the laser surface remelting on the microstructure of a Cu-11.85Al-3.2Ni-3Mn (wt%) SMA. Plates were remelted using three different laser scanning speeds, i.e. 100, 300 and 500 mm/s. The remelted regions showed a T-shape morphology with a mean thickness of 52, 29 and 23 µm and an average grain size of 30, 29 and 23µm for plates remelted using scanning speed of 100, 300 and 500 mm/s, respectively. In the plates remelted with 100 and 300 mm/s some pores were found at the root of the keyhole due to the keyhole instability. We find that the instability of keyholes becomes more pronounced for lower scanning speeds. It was not observed any preferential orientation introduced by the laser treatment.